2018
DOI: 10.1111/jch.13215
|View full text |Cite
|
Sign up to set email alerts
|

Towards better blood pressure: Do non‐pharmacological strategies provide the right path?

Abstract: A scene like this plays out many times every day: A patient with newly diagnosed hypertension, confirmed with out-of-office readings, is seen in the clinic. What happens next depends on the patient, the doctor, and other less understood dynamics of that interaction. In most settings, the patient walks out with a plan to change their lifestyle, a prescription for a pill, or sometimes both. On one hand, most individuals demonstrate significant pill disutility, defined as the longevity gain desired by an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In most trials of sodium reduction, including the Dietary Approach to Stop Hypertension-Sodium trial, the participants received packaged meals, thus representing feeding trials that are not feasible for routine practice. 6 , 7 , 8 Additionally, the source and amount of sodium intake consumed vary across the world. A systematic review reported that Americans consume 3,400 mg (147 mEq) per day, whereas the residents of Northern China consume >11,000 mg (480 mEq) per day.…”
Section: Introductionmentioning
confidence: 99%
“…In most trials of sodium reduction, including the Dietary Approach to Stop Hypertension-Sodium trial, the participants received packaged meals, thus representing feeding trials that are not feasible for routine practice. 6 , 7 , 8 Additionally, the source and amount of sodium intake consumed vary across the world. A systematic review reported that Americans consume 3,400 mg (147 mEq) per day, whereas the residents of Northern China consume >11,000 mg (480 mEq) per day.…”
Section: Introductionmentioning
confidence: 99%